2013
DOI: 10.1080/13504509.2013.856048
|View full text |Cite
|
Sign up to set email alerts
|

Social network effects on the adoption of sustainable natural resource management practices in Ethiopia

Abstract: Soil loss, nutrient depletion and land degradation contribute to the skimpy performance of smallholder agriculture and pose serious policy challenges in developing countries. Surprisingly, natural resource management practices that enhance sustainability while improving productivity have not been fully adopted despite continuous efforts of promotion. Using data collected from 2901 farm households in the Farmers Innovation Fund (FIF) of the World Bank, this study examines factors delaying adoption of resource m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 33 publications
7
60
0
1
Order By: Relevance
“…These results suggest that not only is bridging social capital within the knowledge network potentially positive for innovation, but the links between alters or Bfriends of friends^in the network is also important. This finding is supported by van Rijn et al (2012) who suggested that the larger the network of adopters (direct and indirect links), the greater the likelihood that farmers would adopt innovations due to increased knowledge, access to resource and sources of support (see also Wossen et al 2013).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These results suggest that not only is bridging social capital within the knowledge network potentially positive for innovation, but the links between alters or Bfriends of friends^in the network is also important. This finding is supported by van Rijn et al (2012) who suggested that the larger the network of adopters (direct and indirect links), the greater the likelihood that farmers would adopt innovations due to increased knowledge, access to resource and sources of support (see also Wossen et al 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Recognizing that previous research has identified positive and negative relationships among social capital, information flow, and agricultural innovation in smallholder farming systems (van Rijn et al 2012;Dessie et al 2013;Speranza 2013;Wossen et al 2013;Chen et al 2014), relatively little is known about the nature and extent of social capital in Caribbean agriculture. This is significant because an improved understanding of social capital dynamics within Caribbean smallholder farming systems has been identified as having the potential to inform sustainable natural resource management policy and practice (Adger 2003;Pelling and High 2005) and contribute to regional food and nutrition security objectives (Lowitt et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…The case studies reviewed, for example, range from acceptance of improved crop varieties (Bandiera and Rasul 2006, Van den Broeck and Dercon 2011, Tatlonghari et al 2012, Thuo et al 2014) through the implementation of sustainable and risk-mitigating agricultural practices (Mazzucato and Niemeijer 2000, Conley and Udry 2001, Isaac et al 2007, Matuschke and Qaim 2009, Arora 2012, van Rijn et al 2012, Matouš et al 2013, Wossen et al 2013 to the use of modern information and communication technologies (Butt 2015).…”
Section: Strand (Ii): Agricultural Innovationmentioning
confidence: 99%
“…Network definition: The most frequently investigated social relation is information and advice sharing between farmers and external actors such as extension staff and NGOs (Arora 2012, Matouš et al 2013, Wossen et al 2013. Challenging the assumption that the village level is suitable for defining the reference group for social learning, specific studies compare innovation networks between different study sites, and highlight the role of information exchanges between villages (Mazzucato and Niemeijer 2000, Conley and Udry 2001, Matuschke and Qaim 2009, Isaac et al 2014) and rural and urban areas (Isaac 2012, Wossen et al 2013).…”
Section: Network Operationalizationmentioning
confidence: 99%
See 1 more Smart Citation